Kualitas Layanan Transportasi Umum: Studi Kasus pada Pelayanan Bus Trans Mamminasata Kota Makassar - Putri Dzakilla Handayani; Anisa Fitri; Nina Agustina; Nurul Ayuni; Dewi Sulfa Saguni (PT. Palem Edukasi Nusantara, 2025)
The development of Makassar City as an economic activity center in Eastern Indonesia demands the availability of efficient, safe, and comfortable public transportation for the community. Through the Buy The Service (BTS) policy, the government introduced the Trans Mamminasata Bus as an effort to improve sustainable urban mobility. However, over time, the usage rate of this service has experienced a significant decline, indicating a persistent gap between public expectations and the actual service delivered. This study aims to analyze the service quality of the Trans Mamminasata Bus based on the five dimensions of Servqual: tangibles, reliability, responsiveness, assurance, and empathy. The approach used is descriptive qualitative, with data analysis conducted through the stages of reduction, presentation, and conclusion drawing using the Miles and Huberman model. The results show that the Trans Mamminasata Bus has contributed to improving the quality of public transportation in Makassar through adequate facilities and the implementation of a digital service system. However, issues remain regarding punctuality, inadequate bus stop conditions, and limited service information. Overall, the service quality is considered good but requires improvement in facility maintenance and public outreach. These findings are expected to provide input for local governments and operators in strengthening a public transportation system that prioritizes community satisfaction and ensures service sustainability in the future.